2011
DOI: 10.1126/science.1211485
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pyruvate Kinase M2 by Reactive Oxygen Species Contributes to Cellular Antioxidant Responses

Abstract: Control of intracellular reactive oxygen species (ROS) concentrations is critical for cancer cell survival. We show that, in human lung cancer cells, acute increases in intracellular concentrations of ROS caused inhibition of the glycolytic enzyme pyruvate kinase M2 (PKM2) through oxidation of Cys358. This inhibition of PKM2 is required to divert glucose flux into the pentose phosphate pathway and thereby generate sufficient reducing potential for detoxification of ROS. Lung cancer cells in which endogenous PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
935
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,026 publications
(967 citation statements)
references
References 29 publications
28
935
0
4
Order By: Relevance
“…AMPK inhibits acetyl-CoA carboxylases, inhibiting the consumption of NADPH by fatty acid synthesis and promoting the generation of NADPH by fatty acid oxidation (Jeon et al 2012). High ROS levels in cancer cells also decrease oxidative phosphorylation by promoting glycolysis by stabilizing hypoxia-inducible factor-1 (HIF-1) (Chandel et al 2000;Semenza 2011) or by oxidizing and inhibiting pyruvate kinase M2, diverting glucose into the pentose phosphate pathway (Anastasiou et al 2011). These changes may reflect a broader need to shut down anabolic pathways that generate ROS or consume NADPH in cancer cells experiencing oxidative stress.…”
Section: Cancer Cells Undergo Metabolic Changes To Manage Rosmentioning
confidence: 99%
“…AMPK inhibits acetyl-CoA carboxylases, inhibiting the consumption of NADPH by fatty acid synthesis and promoting the generation of NADPH by fatty acid oxidation (Jeon et al 2012). High ROS levels in cancer cells also decrease oxidative phosphorylation by promoting glycolysis by stabilizing hypoxia-inducible factor-1 (HIF-1) (Chandel et al 2000;Semenza 2011) or by oxidizing and inhibiting pyruvate kinase M2, diverting glucose into the pentose phosphate pathway (Anastasiou et al 2011). These changes may reflect a broader need to shut down anabolic pathways that generate ROS or consume NADPH in cancer cells experiencing oxidative stress.…”
Section: Cancer Cells Undergo Metabolic Changes To Manage Rosmentioning
confidence: 99%
“…The PK gene en codes 2 splic ing vari ants, PKM1 and PKM2. While PKM1 is con sti tu tively ac tive, PKM2 is tun able, be ing al loster i cally ac ti vated by fac tors such as ser ine [46] and fruc tose 1,6 bis pho s phate (FBP) [47] and re pressed by ty ro sine phos pho ry la tion [48], ala nine [49], and ox i da tion [50]. Thus, ac tive PKM2 pro motes gly colytic ATP pro duc tion and in ac tive PKM2 di verts gly colytic in ter me di ates to branched path ways, for ex am ple to the PPP for nu cleotide syn the sis and the pro duc tion of NADPH for re ac tive oxy gen species (ROS) detox i fi ca tion [50].…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…However, an earlier report has indicated that peroxide treatment of cells does result in nuclear localization of PKM2 [5]. This finding also raises the question as to whether the several different post-translational modifications of PKM2 that have been reported, including tyrosyl phosphorylation [1,8], prolyl hydroxylation [9,13], acetylation [14], mono ubiquitination [15], sumoylation [2] and cysteine oxidation [12], are integrated to regulate PKM2's activation of transcriptional programmes [9,10,16] in response to cell signaling events.…”
mentioning
confidence: 44%
“…However, growth stimulation by PKM2 appears to be more subtly regulated than we could have ever imagined. The Cantley laboratory has now elegantly demonstrated that oxidative stress causes oxidation of a critical Cys358 side chain of PKM2 that results in reversible enzyme inactivation and enhanced channeling of glucose metabolites through the pentose phosphate pathway [12]. This diversion serves to generate reducing potential in the form of NADPH that can be used to regenerate reduced glutathione and restore the redox balance of the cell.…”
mentioning
confidence: 99%